Exporter Dynamics Database - Cebeci, Tolga; Fernandes, Ana M.; Freund, Caroline; Pierola, Martha Denisse (2013)
This paper introduces the Exporter Dynamics Database. The database includes exporter characteristics and measures of exporter growth based on firm-level customs information from 38 developing and seven developed countries, primarily for the period between 2003 and 2010. The measures are available at different levels of aggregation, including: a) country-year, b) country-year-product, and c) country-year-destination. Several new stylized facts about exporter behavior across countries emerge from the database. (i) Larger or more developed economies have more exporters, larger and more diversified exporters, and lower entry and exit rates than smaller or developing economies. (ii) In the short run, expansions along the intensive margin (exporter size) contribute more to export growth than expansions along the extensive margin (number of exporters). (iii) Exit rates are highly correlated with entry rates and both are negatively correlated with survival rates, average exporter size, and diversification. (iv) The number of exporters and the entry and exit rates in a country-product group are partially driven by country and product-group effects; however, the average size of exporters in a country-product group is not. Although the first three facts can be explained by models incorporating firm heterogeneity and uncertainty, the fourth fact is more difficult to explain with existing models. Several findings are confirmed in this database, including the importance of large multi-product firms. This database can be a valuable tool to improve the understanding of the micro-foundations of export growth, by providing new insights about exporter characteristics and dynamics.